Aluminum-Induced Alterations in Purinergic System Parameters of BV-2 Brain Microglial Cells - Charles Elias Assmann; Vitor Bastianello Mostardeiro; Grazielle Castagna Cezimbra Weis; Karine Paula Reichert; Audrei de Oliveira Alves; Vanessa Valéria Miron; Margarete Dulce Bagatini; Taís Vidal Palma; Cinthia Melazzo de Andrade; Micheli Mainardi Pillat; Fabiano Barbosa Carvalho; Cristina Ruedell Reschke; et al. (Journal of Immunology Research)
Aluminum (Al) is ubiquitously present in the environment and known to be a neurotoxin for humans. The trivalent free Al anion (Al3+) can cross the blood-brain barrier (BBB), accumulate in the brain, and elicit harmful effects to the central nervous system (CNS) cells. Thus, evidence has suggested that Al increases the risk of developing neurodegenerative diseases, particularly Alzheimer’s disease (AD). Purinergic signaling has been shown to play a role in several neurological conditions as it can modulate the functioning of several cell types, such as microglial cells, the main resident immune cells of the CNS. However, Al effects on microglial cells and the role of the purinergic system remain elusive. Based on this background, this study is aimed at assessing the modulation of Al on purinergic system parameters of microglial cells. An in vitro study was performed using brain microglial cells exposed to Al chloride (AlCl3) and lipopolysaccharide (LPS) for 96 h. The uptake of Al, metabolism of nucleotides (ATP, ADP, and AMP) and nucleoside (adenosine), and the gene expression and protein density of purinoceptors were investigated. The results showed that both Al and LPS increased the breakdown of adenosine, whereas they decreased nucleotide hydrolysis. Furthermore, the findings revealed that both Al and LPS triggered an increase in gene expression and protein density of P2X7R and A2AR receptors, whereas reduced the A1R receptor expression and density. Taken together, the results showed that Al and LPS altered the setup of the purinergic system of microglial cells. Thus, this study provides new insights into the involvement of the purinergic system in the mechanisms underlying Al toxicity in microglial cells.